Fine Scale Patterns of Population Structure and Connectivity in Scandinavian Flat Oysters in Scandinavia (Ostrea edulis L.) - Chloé Robert; Homère J. Alves Monteiro; Alan Le Moan; Arnaud Tanguy; Ane T. Laugen; Jakob Hemmer‐Hansen; Åsa Strand; Pierre De Wit (Evolutionary Applications)
ABSTRACT Stocks of the European flat oyster, Ostrea edulis, have collapsed due to overfishing, habitat destruction, and pathogen outbreaks across most of their distribution range. Nonetheless, as a result of lower exploitation pressure and the absence of pathogens in the most northern part of the range, a large part of the remaining wild population can be found in relatively high densities in Scandinavia, a region in Northern Europe. However, despite recent studies focusing on flat oyster population structure along the European coast, little is known about the population structure of oysters in the Skagerrak marginal sea in Scandinavia, and how it is related to neighbouring regions. This study, therefore, aimed to investigate the population structure of flat oysters in Scandinavia, with a special emphasis on the Skagerrak. We gathered low‐coverage whole‐genome sequencing data from oysters in Sweden, Norway, and Denmark, the three countries that border the Skagerrak. Genetic diversity appeared to be homogeneously distributed over the sampled area in the Skagerrak, while samples collected from the east coast of Denmark and from a location with known historical farming activity on the Norwegian West Coast were genetically distinct from Skagerrak samples. A genetic barrier analysis indicated barriers to gene flow in the Baltic Sea transition zone and on the west coast of Norway. Overall, our results suggest that flat oysters from the Swedish Skagerrak coasts form a single panmictic population that is distinct from neighbouring seas, potentially allowing for regional management of stocks and restoration translocations in the area. However, the genetic composition of donor and recipient stocks should be assessed on a case‐by‐case basis, genetic diversity effects of hatchery practices should be monitored, and biosecurity measures need to be considered prior to any movement of stock.